Temperature and Humidity Control System for Tempe Gembus Fermentation Process Based on Internet of Things - Riski Sinta Sari; Nuryanto Nuryanto; Andi Widiyanto (Urecol Journal. Part G: Multidisciplinary Research, 2021)
Tempe gembus is made from tofu dregs which are fermented by tempe mushrooms rhizopus sp. Fermentation process of tempe gembus using conventional method takes 2 days 1 night/about 36-48 hours with temperatures between 25oC-35oC, humidity 60-80%. To maintain temperature and humidity stability by covering the cloth and opening the cloth. This research will discuss how to maintain temperature and humidity automatically using the ESP8266 microcontroller which controls the temperature and humidity sensors using DHT11. When the temperature is below 35 Â°C the system will perform an automatic action in the form of a light on. When the temperature is above 35 Â°C, the system will automatically turn on the fan until the temperature returns to normal. The output of this system is displayed on thingspeak and can be seen through thingsview which can be accessed via a smartphone by utilizing the wireless features found on the ESP8266. Tempe gembus fermentation is strongly influenced by the temperature and humidity of the fermentation room. The test results show that using an automatic control system is 16 hours faster than conventional methods.